PENGARUH CORPORATE GOVERNANCE, UKURAN PERUSAHAAN SERTA LEVERAGE TERHADAP KINERJA KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Zulhelmy; Sukma (Journal Of Islamic Finance And Accounting Research, 2022)
This study aims to find empirical evidence regarding the Effect of Corporate Governance consisting of the Board of Directors, Board of Commissioners Size, Audit Committee, Company Size and Leverage on Company Financial Performance (Study on Financial Institution Sub-Sector Service Companies Listed on the Indonesia Stock Exchange in 2017 -2019). This study uses purposive sampling method as a sample selection method. The population of this study is a service company sub-sector of financial institutions as many as 19 companies listed on the Indonesia Stock Exchange (IDX). Based on predetermined criteria, 16 companies were sampled in this study. Hypothesis testing in this study using multiple regression analysis techniques.The results show that partially the Board of Directors, the size of the Board of Commissioners and the Audit Committee have no significant effect on financial performance, firm size has a positive effect on financial performance, and leverage has a negative effect on financial performance. and simultaneously the Board of Directors, Board of Commissioners Size, Audit Committee, Company Size, Leverage have a significant effect on the company's financial performance.